Impacts of thickness reduction and heat treatment on the optical properties of thin chalcogenide films. Issue 14 (1st October 2017) - Adam, A.M.; Petkov, P.
Abstract: Bi-based chalcogenides, in the form of thin crystalline films, were deposited at different thicknesses onto highly cleaned glass slides with the aid of vacuum thermal evaporation technique. The influence of thermal annealing on the optical properties of Bi2 Te3 -Bi2 Se3 films at different thicknesses is investigated in this work. Wavelength dependence of the optical transmittance and reflectance was recorded, for the as-prepared and the annealed films, in the wavelength range from 350 to 2700 nm using a double beam spectrophotometer. Fundamental optical properties such as absorption coefficient and energy band gap were derived based on the measured spectra and film's thickness. We demonstrate in the present work that the synergy of annealing and thickness reduction can be exploited for light transmittance enhancements, and consequently for optoelectronic applications including transparent conductive electrodes.